Electron-beam irradiation of cinnamate films affords nanoscale patterned substrates for use in devices and as scaffolds in tissue engineering - Strunk, Karl-Philipp; Bojanowski, Maximilian; Huck, Christian; Bender, Markus; Veith, Lisa; Tzschoppe, Michael; Freudenberg, Jan; Wacker, Irene; Schröder, Rasmus R.; Pucci, Annemarie; Melzer, Christian; Bunz, Uwe H. F. (ACS applied nano materials, 2020)
The fabrication of electronic, photonic, and metamaterial-based devices, or tissue engineering requires the controlled deposition and patterning of materials. Electron-beam lithography (EBL) offers unprecedented miniaturization of those devices because of its high resolution. We present a concept to induce a classic photochemical reaction in condensed matter via EBL. We investigate the response of a tetrameric cinnamate monomer in thin films toward photon and electron radiation. In the solid state, photoexcitation and electron bombardment similarly induce [2 + 2] cycloadditions, forming insoluble truxilic acid esters, as shown via IR spectroscopy measurements. Subsequently, we employed the investigated material as an electron-beam resist, showing resistance against wet-chemical etchants. Structures with resolution down to 60 nm were obtained, not achievable with conventional photolithography, proving that [2 + 2] cycloaddition of cinnamic acid containing compounds is suitable for applications in the field of EBL.
Gesehen am 08.10.2020